2021
DOI: 10.1111/eva.13284
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome sequencing reveals the artificial selection and local environmental adaptability of pigeons (Columba livia)

Abstract: To meet human needs, domestic pigeons ( Columba livia ) with various phenotypes have been bred to provide genetic material for our research on artificial selection and local environmental adaptation. Seven pigeon breeds were resequenced and can be divided into commercial varieties (Euro‐pigeon, Shiqi, Shen King, Taishen, and Silver King), ornamental varieties (High Fliers), and local varieties (Tarim pigeon). Phylogenetic analysis based on population resequencing showed that one group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…The results of the present study revealed that the key genes associated with the BW, BS and PT of meat pigeons included NCAPG / LCORL , IGF2BP3 and MSTN . Previous studies of selective breeding of meat pigeons and local breeds have also reported that NCAPG / LCORL is associated with BS (Hou et al., 2022). Therefore, NCAPG / LCORL has been targeted for artificial breeding of meat pigeons owing to the high correlations with BW, BL, KL and SL, demonstrating genetic pleiotropy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The results of the present study revealed that the key genes associated with the BW, BS and PT of meat pigeons included NCAPG / LCORL , IGF2BP3 and MSTN . Previous studies of selective breeding of meat pigeons and local breeds have also reported that NCAPG / LCORL is associated with BS (Hou et al., 2022). Therefore, NCAPG / LCORL has been targeted for artificial breeding of meat pigeons owing to the high correlations with BW, BL, KL and SL, demonstrating genetic pleiotropy.…”
Section: Discussionmentioning
confidence: 90%
“…Genome-wide association study of growth traits and validation of key mutations (MSTN c.C861T) associated with the muscle mass of meat pigeons (Bian et al, 2020;Gazda et al, 2018). Genome sequencing and bioinformatics analysis have revealed various genes related to the artificial selection and adaptability of farmed pigeons (Hou et al, 2022). The breeding of meat pigeons, like other livestock and poultry, is largely focused on reproductive performance, growth, development and meat quality.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…We detected differences in body mass among laurel and pine forest common chaffinches and we detected several genes involved in growth and body size, including apobec2 (Sato et al, 2010), cast (Zhang et al, 2012) and plppr5 (Hou et al, 2022), and genes involved in skeleton and bone formation including prr5l , (Wallace et al, 2022), cap2 (Kepser et al, 2019) and epha5 (Yamada et al, 2013). We also detected differences between both habitats in wing length, and we found as a candidate the cux1 gene, which has been shown to be involved in the regulation of joint formation in the limb development of chicks (Lizarraga et al, 2002) and is related to small wings in the flightless Galapagos cormorant (Burga et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Another bird species which has been bred for different purposes, including ornamental, production, competition, and experimental uses, is the domestic pigeon ( Columbia livia ). By using whole‐genome sequences of animals from seven breeds it has been revealed that the genetic diversity and inbreeding levels of domestic pigeons are consistent with human‐driven selection, indicating that genomic regions under selection in commercial populations for production harbor genes associated to body size, reproduction, and feather color; while in ornamental populations genes are mostly related to skeletal‐muscle features, potentially affecting appearance traits (Hou et al, 2021 ). These studies provide further insights into the impact of domestication and artificial selection in shaping the genome of terrestrial domestic animals, which represent valuable knowledge for within‐species genetic diversity conservation and selective breeding.…”
Section: Domestication and Artificial Selectionmentioning
confidence: 99%